2001
DOI: 10.18061/dsq.v21i1.256
|View full text |Cite
|
Sign up to set email alerts
|

Postsecondary Education Services and Employment Outcomes within the Vocational Rehabilitation System

Abstract: This article examines provision of postsecondary education services by the Vocational Rehabilitation (VR) system to eligible individuals with disabilities nationwide. The results of a secondary analysis of elements of the RSA-911 database from the Rehabilitation Services Administration in FY 1997 are discussed. The extent to which individuals within the VR system receive postsecondary education services is compared to the rate of individuals with and without disabilities participating in postsecondary educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 6 publications
3
19
1
Order By: Relevance
“…Menard (2002) cautioned that large samples may yield statistically significant relationships but with nonsubstantively significant effects and has little importance. Still, the current finding supports a study by Gilmore, Schuster, Zafft, and Hart (2001) who reported that college and university training had no impact on whether consumers achieved competitive employment. In fact, vocational outcomes of consumers were compared for those who received college and university training, business and vocational training, both college and business training, and no postsecondary education.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Menard (2002) cautioned that large samples may yield statistically significant relationships but with nonsubstantively significant effects and has little importance. Still, the current finding supports a study by Gilmore, Schuster, Zafft, and Hart (2001) who reported that college and university training had no impact on whether consumers achieved competitive employment. In fact, vocational outcomes of consumers were compared for those who received college and university training, business and vocational training, both college and business training, and no postsecondary education.…”
Section: Discussionsupporting
confidence: 88%
“…Once again, a chi-square analysis was used to conclude that consumers identifying as European American received more college and university training than those classified in a group identifying as African American, Asian, Native Hawaiian or Pacific Islander, and Hispanic. In considering disability, Gilmore and Bose (2005) stated that 35% of consumers with orthopedic impairments received college and university training; however, fewer consumers from all other impairment types received college and university training. Elmore Williams (2008) reported in a dissertation that VR consumers identifying as African American with specific learning disabilities were less likely to receive college and university training than similar consumers who identified as European American.…”
Section: Receiving College and University Trainingmentioning
confidence: 99%
“…This approach results in more individuals with $0.00 annual earnings being included in the calculation. This study's approach to calculating annual wage data also is more conservative than approaches typically used in other studies on employment outcomes, which often calculate annual wages based on consumer report, or hourly/weekly wages within a short time period post-exit (Gilmore & Bose, 2005;Gilmore, Bose, & Hart, 2001;Newman, Wagner, Cameto, & Knokey, 2009). Estimates of total annual wages based on hourly or weekly data assume that the person is working full time throughout a year.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in one analysis, individuals who received any postsecondary education services through VR (32.6% of consumers) were almost twice as likely to earn high wages as low wages (30.8% vs. 16.0%), and both receipt of postsecondary services through VR and completion of some level of postsecondary education significantly predicted higher earnings (Schmidt-Davis et al, 2000). Yet, Gilmore, Schuster, et al (2001) found that less than a quarter (21%) of all VR consumers participated in any form of postsecondary education, ranging from short-term occupational training programs to 4-year colleges.…”
mentioning
confidence: 99%
“…Over the last decade, researchers have found that participation in PSE for VR clients with significant disabilities (including those with ID), correlated positively with competitive rather than sheltered employment (Gilmore, Schuster, Zafft, & Hart, 2001). Further, participating in any type of PSE enables students to explore interests and learning skills they may not develop in high school or through work experiences (Schneider, 2000).…”
Section: Limited Vr Support For Individuals With Idmentioning
confidence: 99%